Treatment of halogenated organic compounds and monitoring of microbial dynamics in up-flow fixed bed reactors under sequentially alternating pollutant scenarios - Emanuelsson, Maria A. E. (2010)
Two up-flow fixed bed reactors (UFBR) were operated for 8 months treating a model synthetic wastewater containing 2-fluorobenzoate (2-FB) and dichloromethane (DCM). The stability of the reactors under dynamic conditions, that is, sequentially alternating pollutants (SAP), shock loads, and starvation periods was assessed. Two support materials were used: expanded clay (EC) that does not adsorb 2-FB or DCM, and granular-activated carbon (GAC) that adsorbs 180 mg gg⁻¹ of 2-FB and 390 mg gg⁻¹ of DCM. The reactors were inoculated with a 2-FB-degrading strain (FB2) and a DCM degrader (TM1). 2-FB was fed at organic loads ranging from 0 to 800 mg L⁻¹ d⁻¹, while DCM was fed at 0–250 mg L⁻¹ d⁻¹. 2-FB or DCM were never detected at the outlet of the GAC reactor, while in the EC reactor outlet small amounts were observed. Nevertheless, the highest biological elimination capacity was observed in the EC reactor (over 700 mg L⁻¹ d⁻¹ of 2-FB). DGGE analysis revealed a fairly stable bacterial community with the largest shifts occurring during starvation periods and changes in feed composition. Several bacterial strains isolated from the reactors showed capacity for 2-FB degradation, while only strain TM1 degraded DCM.